Etika Berkeluarga, Bermasyarakat, dan Berpolitik dalam Penafsiran - Aghisna Rahmatika; Siska Lailan Munira RKT; Restu Permohonan Hasibuan; Jendri Jendri (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This article discusses ethics in three domains of life: family, society, and politics. Family ethics emphasizes the importance of noble values ​​such as love, mutual respect and responsibility in building harmonious relationships. Community ethics encourages attitudes of tolerance, mutual cooperation and concern for others to create a peaceful and prosperous social life. Political ethics focuses on the principles of justice, honesty and accountability in running government to achieve shared prosperity. These three domains are interrelated and influence each other, so it is important to build strong ethics in each domain in order to create a civilized, just and prosperous society.